The Genealogy of Pura Agung Surya Bhuvana in Jayapura, Papua - I Wayan Rai; I Gusti Made Sunartha; Ida Ayu Made Purnamaningsih; Ni Made Ruastiti; Yunus Wafom (UNHI PRESS, 2020)
Pura Agung Surya Bhuvana in Jayapura is the eastern part of Padma Buana temple. Its establishment was initiated by Balinese Hindus and has become the center of Balinese Hindu socio-cultural activities and an important icon of Jayapura. This article discusses the establishment of Pura Agung Surya Bhuvana from the beginning and its development into the center of Balinese Hindus’ social and cultural-religious activities in Jayapura of Papua. This article based on qualitative research, in which all data was collected through observation, document studies, interviews, and FGD with several members of the pengempon (the temple’s servants) as informants and observers of Papuan culture. Data analyzed descriptively by applying symbol theory and structural-functional theory. The results showed that Hindus established the Pura Agung Surya Bhuvana at Jayapura in 1962. Before, the Hindus of Papua, whose dominantly Balinese migrant, carried out religious activities at Matra’s house. I Made Matra was a civil servant at the Papua Province government office. Over time, the number of Hindus who migrate to the city of Jayapura continues to increase. Therefore in 1979, Hindu leaders in Jayapura built the Pura Agung Surya Bhuvana for the needs of Hindus. Pura Agung Surya Bhuvana was built on Skyline hill in 1982 and it was inaugurated in 1990. In 2012, the Pura Agung Surya Bhuvana was renovated to be more majestic than before, and later on became a center of Hindu worship, the center of Balinese socio-cultural activities, arts center, Hindu religious education centers, and tourist attractions in Papua.